Building Healthy Financial Habits And Maintaining Mental Health Students Senior High School Taught Financial Planning Education - Nuraini; Marlya Fatira AK; Indri Dithisari; Mik Salmina; Sri Nirmala Sari; Salsabila (ALTSA Publisher, 2024)
This activity aims to provide an understanding of the basic steps in financial planning, managing expenses wisely, building healthy financial habits, and maintaining mental health when facing financial problems. This service uses a descriptive and qualitative approach, where the data collected is analyzed to provide solutions to the issues faced by students. After the Socialization and Education of Financial Planning for Students at SMKS Dharma Patra Pangkalan Susu, the average score of students who feel that they understand more about the importance of recording expenses in detail to manage finances, feel able to distinguish needs and desires, motivation to buy goods wisely, including waiting for a discount moment to save the costs, starting to plan expenses so that they are always smaller than their income, Committed to setting aside some money for unexpected needs or future savings is 86% of the 25 students, This shows a significant increase compared to the initial condition, which is 79%. The educational activities succeeded in overcoming two main problems faced by students, namely consumptive behavior and the impact of financial management on mental health and learning achievement. Through counseling on personal financial planning, students gain understanding and skills in managing finances wisely, managing expenses, and building healthy financial habits, which has a positive impact on increasing their financial awareness. In addition, with a holistic approach that includes material on the relationship between finances and mental health, students can also reduce stress and anxiety that disrupt mental balance and study concentration. As a result, most students feel calmer, more confident, and more motivated to face daily challenges and learn more effectively.